MENINGKATKAN HASIL BELAJAR SISWA KELAS III DI SDN 49 OKU PADA MATERI MEYAKINI ALLAH MAHA ESA MELALUI PENERAPAN METODE MAKE A MATCH - Janalia Janalia; Tutut Handayani; Yuyun Sartinah (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2023)
The purpose of this research was to find out whether there was an increase in the learning outcomes of grade 3 students at SDN 49 OKU in the material Believing in Allah Almighty after applying the Make A Match type of cooperative learning method. In the application of the Make A Match method to ongoing learning, the learning outcomes achieved by 3rd graders of SDN 49 OKU in the form of cognitive, affective, and psychomotor abilities related to the subject matter of PAI Fear of God Almighty, showed an increase with the acquisition of a score from cycle I of 59 .2% and cycle II of 88.8%. This shows an increase from cycles I and II. These results indicate that classroom action research conducted from the initial conditions to the end of cycle II shows an increase in student learning outcomes. Based on the results of the Classroom Action research, it can be concluded that: There is an increase in the learning outcomes of grade 3 students at SDN 49 OKU in the material Believing in Allah Almighty after applying the Make A Match learning model.